Determining the Pathogenicity of a Genomic Variant of Uncertain Significance Using CRISPR/Cas9 and Human-Induced Pluripotent Stem Cells. Issue 23 (4th December 2018) - Ma, Ning; Zhang, Joe Z.; Itzhaki, Ilanit; Zhang, Sophia L.; Chen, Haodong; Haddad, Francois; Kitani, Tomoya; Wilson, Kitchener D.; Tian, Lei; Shrestha, Rajani; Wu, Haodi; Lam, Chi Keung; et al.
Abstract : Background: The progression toward low-cost and rapid next-generation sequencing has uncovered a multitude of variants of uncertain significance (VUS) in both patients and asymptomatic "healthy" individuals. A VUS is a rare or novel variant for which disease pathogenicity has not been conclusively demonstrated or excluded, and thus cannot be definitively annotated. VUS, therefore, pose critical clinical interpretation and risk-assessment challenges, and new methods are urgently needed to better characterize their pathogenicity. Methods: To address this challenge and showcase the uncertainty surrounding genomic variant interpretation, we recruited a "healthy" asymptomatic individual, lacking cardiac-disease clinical history, carrying a hypertrophic cardiomyopathy (HCM)-associated genetic variant (NM_000258.2:c.170C>A, NP_000249.1:p.Ala57Asp) in the sarcomeric gene MYL3, reported by the ClinVar database to be "likely pathogenic." Human-induced pluripotent stem cells (iPSCs) were derived from the heterozygous VUS MYL3 (170C>A) carrier, and their genome was edited using CRISPR/Cas9 to generate 4 isogenic iPSC lines: (1) corrected "healthy" control; (2) homozygous VUS MYL3 (170C>A ) ; (3) heterozygous frameshift mutation MYL3 (170C>A/fs ) ; and (4) known heterozygous MYL3 pathogenic mutation (NM_000258.2:c.170C>G), at the same nucleotide position as VUS MYL3 (170C>A), lines. Extensive assays including measurements of gene expression, sarcomere structure, cell size, contractility, action potentials, and calcium handling were performed on the isogenic iPSC-derived cardiomyocytes (iPSC-CMs). Results: The heterozygous VUS MYL3 (170C>A) -iPSC-CMs did not show an HCM phenotype at the gene expression, morphology, or functional levels. Furthermore, genome-edited homozygous VUS MYL3 (170C>A) - and frameshift mutation MYL3 (170C>A/fs) -iPSC-CMs lines were also asymptomatic, supporting a benign assessment for this particular MYL3 variant. Further assessment of the pathogenic nature of a genome-edited isogenic line carrying a known pathogenic MYL3 mutation, MYL3 (170C>G), and a carrier-specific iPSC-CMs line, carrying a MYBPC3 (961G>A) HCM variant, demonstrated the ability of this combined platform to provide both pathogenic and benign assessments. Conclusions: Our study illustrates the ability of clustered regularly interspaced short palindromic repeats/Cas9 genome-editing of carrier-specific iPSCs to elucidate both benign and pathogenic HCM functional phenotypes in a carrier-specific manner in a dish. As such, this platform represents a promising VUS risk-assessment tool that can be used for assessing HCM-associated VUS specifically, and VUS in general, and thus significantly contribute to the arsenal of precision medicine tools available in this emerging field. Abstract : Supplemental Digital Content is available in the text.